2014
DOI: 10.1177/1545968314550369
|View full text |Cite
|
Sign up to set email alerts
|

Sirract

Abstract: Background Walking-related disability is the most frequent reason for inpatient stroke rehabilitation. Task-related practice is a critical component for improving patient outcomes. Objective To test the feasibility of providing quantitative feedback about daily walking performance and motivating greater skills practice via remote sensing. Methods In this phase III randomized, single blind clinical trial, patients participated in conventional therapies while wearing wireless sensors (tri-axial accelerometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 23 publications
0
54
2
1
Order By: Relevance
“…Two trials to increase walking activity through monitoring and feedback in rehabilitation of stroke patients have recently been published [29, 30]. In contrast to our study, no significant increase in walking time in the intervention group was reported.…”
Section: Discussioncontrasting
confidence: 99%
“…Two trials to increase walking activity through monitoring and feedback in rehabilitation of stroke patients have recently been published [29, 30]. In contrast to our study, no significant increase in walking time in the intervention group was reported.…”
Section: Discussioncontrasting
confidence: 99%
“…43,44 Internet-connected mHealth tools include mobile telecommunications between medical professionals and their patients. Smartphones, for example, enable text messaging, conference calls with video, instructional video recordings, and visual and spoken feedback between patients and investigators, therapists or a social support group.…”
Section: Solutionsmentioning
confidence: 99%
“…In addition, wearable sensors with algorithms that recognize activity patterns can identify the type, quantity and aspects of quality of movements during skills practice and daily activities. 43,44 To date, body sensors have been underutilized for health care purposes, but they are likely to become ubiquitous. 45 …”
Section: Solutionsmentioning
confidence: 99%
See 2 more Smart Citations